2015
DOI: 10.1016/j.mce.2014.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Expression of FSH receptor in the hamster ovary during perinatal development

Abstract: FSH plays an important role in ovarian follicular development, and it functions via the G-protein coupled FSH receptor. The objectives of the present study were to determine if full-length FSHR mRNA and corresponding protein were expressed in fetal through postnatal hamster ovaries to explain the FSH-induced primordial follicle formation, and if FSH or estrogen (E) would affect the expression. A full-length and two alternately spliced FSHR transcripts were expressed from E14 through P20. The level of the full-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…This finding indicated that M-CSF may sensitize GCs to the stimulatory effect of FSH and assist in follicular growth. Chakraborty et al (24) suggested that FSHR is expressed in the foetal hamster ovary to account for FSH-induced primordial follicle formation and cyclic AMP production. It was previously demonstrated that M-CSF facilitated the production of E 2 .…”
Section: Discussionmentioning
confidence: 99%
“…This finding indicated that M-CSF may sensitize GCs to the stimulatory effect of FSH and assist in follicular growth. Chakraborty et al (24) suggested that FSHR is expressed in the foetal hamster ovary to account for FSH-induced primordial follicle formation and cyclic AMP production. It was previously demonstrated that M-CSF facilitated the production of E 2 .…”
Section: Discussionmentioning
confidence: 99%
“…As we all know, in the follicular phase, gonadotropins especially FSH can enhance the production of estrogen in granulosa cells (Erickson & Hsueh 1978, Jamnongjit & Hammes 2006. Besides, with the follicle development, the estrogen secretion increases and then activates the FSH receptor expression (Chakraborty & Roy 2015). We observed that, after ovary fat pad removal, the estrogen level decreased and Fshr expression was downregulated (Fig.…”
Section: Discussionmentioning
confidence: 66%
“…Under these circumstances, the increased expression of FSHR in the POAT-deficient ovaries might be a compensatory response to restore follicle growth. The compensatory increase in FSHR was also found in FSH antiserum-treated hamsters, in which FSH antiserum markedly reduced serum FSH while Fshr mRNA was slightly increased to restore the FSH signaling in ovarian cells (Chakraborty & Roy 2015). It seemed that the compensatory increase of FSHR expression was common in the condition of FSH deficiency.…”
Section: Discussionmentioning
confidence: 82%